The Influence of Image and Reputation on the Competitiveness of Political Party - Dedeh Maryani; Marcellia Susan; Ratih Hurriyati (International Journal of Science and Society, 2020)
The objective of this study is to describe the influence of image and reputation on the competitiveness of a political party. This study uses a quantitative approach with explanatory survey method design, the entire community of West Java Province who has suffrage on the election is the population by taking 400 respondents for the samples, while the random multistage cluster is used as the sampling. Data analysis used in this study is descriptive and verification analyzes, while Partial Least Square (PLS) is used for the hypothesis test. The result shows that there is a significant positive influence of the independent variable of the image of a political party (X1) and variable of the reputation of a political party (X2) on the dependent variable, the competitiveness of political party (Y). We recommend that the image of a political party must be built continuously in order to build a high long-term reputation of the political party, and eventually, it will make the high competitiveness of the political party. It can be done through various programs for the community that could make public trust in political parties increase, for example, the policies made by the government altogether with the legislature must be in favor of the interests of the community. The limitation of this study is the marketing of politics. This is an earlier analysis result.